ISOLATION AND IDENTIFICATION OF ENDOPHYTIC BACTERIA PRODUCING BRIGHT RED PIGMENT FROM THE DYE YIELDING PLANT BETA VULGARIS L - Khanam, Bushra; Chandra, Ramesh (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objectives: Isolation of endophytic bacteria from the of Beta vulgaris L. for production of pigment. Characterization of isolated bacterial endophyte with respect to morphological, biochemical and molecular biological aspects which lead to their identification. Methods: Plant materials were sterilized by standard methods. Isolation of bacterial endophyte using nutrient media was carried out. Sterility check of explants was performed using two techniques. Morphological, biochemical and molecular biology methods were employed for identification of isolated endophyte. Light microscopy and scanning electron microscopy, molecular gene sequencing was performed on endophytic isolate KC1. Phylogenetic tree was constructed to find the similarity of KC1 and other bacteria. Results: The isolate KC1 was found acoccobaccilus, gram negative, which gave a catalase positive reaction and after molecular identification, it was designated as Serratiamarcescens strain VIT-PTS (GenBank Accession Number: KJ716445.1) Conclusion: The results indicate that 17 endophytic bacteria are isolated out of that one bacterial isolate KC1 secretes red pigment. Based on the phylogenetic analysis of 16S rRNA gene sequences, isolate KC1 and Serratiamarcescens were in the same terminal clade. This bacterial pigment, which is expected to be prodigiosin, is promising as potential textile and food colorant. Â